Adolescent-onset X-linked Adrenoleukodystrophy Presenting as Treatment-resistant Bipolar Disorder - Ray, Anirban (Indian J Psychol Med, 2017)
A small proportion of bipolar disorder of adolescent onset can be secondary to underlying neurological disorder (secondary mania). We report a case of treatment-resistant mania secondary to cerebral form of adrenoleukodystrophy of adolescent onset. This case demonstrates the need for clinicians to be alert to the possibility of rare neurological diseases that can present with psychiatric manifestations.